SISTEM PAKAR BERBASIS WEB UNTUK MENDIAGNOSA PENYAKIT KULIT - Paryati Paryati (Telematika, 2011)
Human skin consists of various layers either protected or very sensitive to outside attack such as from the surrounding. Today there are many inventions in connection with the skin disease where many skin bacterias and viruses attack the human either from the surroundings, climate or temperature even from direct contact with the wet nurse or mother of virus. Skin disease which is suffered by the people is easy to wide spread because of lack information and knowledge about skin disease. This system is made in order that the skin sufferers know and understand the kind of skin disease which they get and this system gives some solutions and preventions in accordance with the disease circle. The method which is used in the plan and development is waterfall method. The application which is used to make this expert system programme is Dreamweaver, XAMPP, Adope Photoshop, Mysql, Opera. The result of this research is in the form of application programme that can help the user know the kinds of skin disease and also know the technique or theraphy and the way of prevention.